(3CKQ GdJZjjQ aj bjeI GdfbhOYdi GdGdJRGeGJ aj Gdabg GdGSdGej (B:s (3OQGSI ebGQfI (B/s - (3GdTGYQ, eMehO OjGHs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2004)
1) (3JYQja GdfbhO h GdhVY GdGbJUGOj dgG (B: (3JYQja GdfbhO h GdJWhQ GdJGQjNj dgG h GdhVY GdGbJUGOj ddfbhO h GdSjGSI GdfbOjI h CSHGH GdJZjjQ aj bjeI GdfbhO , GdhVY Gdabgj ddadhS h GdGhQGb GdfbOjI (B2)(3GdGdJRGeGJ h eUGOQgG h CMcGegG (B: (3MbjbI GdGdJRGe h CQcGfg h eUGOQgh CMcGe GdGdJRGe (B3) (3CKQ GdJZjjQ aj bjeI GdfbhO Ydi GdGdJRGeGJ (B: (3CKQ GdJZjjQ aj bjeI GdfbhO GdNdbjI , GdPgH h GdaVI h CKQ GdJZjjQ aj bjeI GdfbhO GdGUWdGMjI Ydi GdGdJRGeGJ (B.s
Keywords: (3GdEdJReGJs; (3GdbjeI `` fbhOs; (3GdfbhO `` Gdabg GdGSdGejs